Methods for isolating atrial cells from large mammals and humans. (September 2015) - Voigt, Niels; Pearman, Charles M.; Dobrev, Dobromir; Dibb, Katharine M.
Abstract: The identification of disturbances in the cellular structure, electrophysiology and calcium handling of atrial cardiomyocytes is crucial to the understanding of common pathologies such as atrial fibrillation. Human right atrial specimens can be obtained during routine cardiac surgery and may be used for isolation of atrial myocytes. These samples provide the unique opportunity to directly investigate the effects of human disease on atrial myocytes. However, atrial myocytes vary greatly between patients, there is little if any access to truly healthy controls and the challenges associated with assessing the in vivo effects of drugs or devices in man are considerable. These issues highlight the need for animal models. Large mammalian models are particularly suitable for this purpose as their cardiac structure and electrophysiology are comparable with humans. Here, we review techniques for obtaining atrial cardiomyocytes. We start with background information on solution composition. Agents shown to increase viable cell yield will then be explored followed by a discussion of the use of tissue-dissociating enzymes. Protocols are detailed for the perfusion method of cell isolation in large mammals and the chunk digest methods of cell isolation in humans. Highlights: The isolation method needs to be adapted to the experimental aims. Separation of myocytes requires perfusion with Ca 2 + -free buffers. Ca 2 + -free perfusion causes cell damage during reintroduction of Ca 2 + (Ca 2 + paradox). Several procedures are used to protect myocytes from detrimental effects of the Ca 2 + paradox. Breakdown of extracellular matrix requires enzymatic digestion.